Association of risk factors of type 2 diabetes mellitus and fasting blood glucose levels among residents of rural area of Delhi: a cross sectional study - Adhikary, Mrinmoy; Chellaiyan, Vinoth Gnana; Chowdhury, Ranadip; Daral, Shailaja; Taneja, Neha; Das, Timiresh Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes mellitus has reached epidemic proportions globally. India has largest number of diabetic population constituting major proportion worldwide. The epidemic of diabetes in India is due to the rapid epidemiological transition attributed to changes in dietary patterns and decreased physical activity apart from the role of genetic factors in the disease causation. The objectives of the study was to assess the risk factors of type 2 diabetes and to find the relation between risk factors of type 2 diabetes and fasting capillary blood glucose level among the study population. Methods: A cross sectional community based study was carried out using a semi structured, pretested, questionnaire among 432 study subjects aged 30 years and above in a randomly selected sahoorpur village under Fatehpur Beri primary health centre. The study duration was from March 2011 to February 2012. Means and proportions were calculated. Multivariate logistic regression was applied. Results: The mean (SD) age of the study population was 45 (±11.9) years. Positive family history of Diabetes was present in 14.4% of study population. History of smoking and alcohol was found in 37.5% and 8.3% respectively. Prevalence of overweight and obesity was 48.8% and 17.2% respectively. Regression showed age more than 60 years (OR 1.135, 95% CI 0.037 – 0.492), family history of diabetes (OR 4.181, 95% CI 1.734 – 10.083), higher waist circumference (OR 13.414, 95% CI 4.991 – 36.051), sedentary work (OR 3.133, 95% CI 0.032 – 0.592), obesity (OR 4.709, 95% CI 1.790 – 12.394) had higher odds of having higher fasting capillary blood glucose level. Conclusions: The study found a higher prevalence of risk factors among the study population. Risk factors showed a significant relation with higher fasting capillary blood glucose. There is a mandate for health education to motivate change in lifestyle modification among the study population.